Tour Guide Simulation: A Task-Based Learning Activity to Enhance Young Thai Learners’ English (Malaysian Journal of Learning and Instruction, 2019)
Purpose - This study aimed to explore the effects of task-based language teaching (TBLT) with a tour guide simulation as a focused activity on young Thai learnersâ€™ English speaking skill and their attitudes towards the instruction. Methodology - Based on a three-phase framework (i.e., pre-task, during-task, and post-task), TBLT was implemented with a Grade 4 class for a period of eleven weeks. Initially, a set of English lessons developed based on the context of local tourist attractions was implemented at the pre-task stage. In the second stage, a simulated tour guide task was used to assess their ability to turn the language input into a practical and authentic use of English speaking. Subsequently, corrective feedback on each studentâ€™s performance was provided, and their attitudes towards the instruction were examined at the last stage. Findings - The students were able to satisfactorily complete the tour guide task in English, indicating the potential of the task as a device to strengthen their speaking skill. Moreover, they generally had a favourable attitude towards the instruction. Significance - These findings are significant for both school teachers and curriculum designers. In addition to confirming the effectiveness of TBLT, this study highlights the promising use of context specific-based lessons and class activities as an avenue for young learners to practice speaking English in a context relevant to them.